Implementasi Nilai-Nilai Agama dan Moral Pada Anak Usia Dini di TK IT Bunayya 7 Desa Laut Dendang Kec Percut Sei Tuan Kab Deli Serdang - Lonita Hasraini Siregar; Khadijah Khadijah; Zulkipli Nasution (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This research aims to determine the religious and moral values ​​program for early childhood at TK IT Bunayya 7 Laut Dendang Village, Percut Sei Tuan District, Deli Serdang District. The research method in this thesis uses descriptive qualitative research. The subjects in this research were class teachers, accompanying teachers and students at the IT Bunayya Kindergarten school 7 Laut Dendang Village, Percut Sei Tuan District, Deli Serdang District. The process of data collection techniques using observation, interviews and documentation. The results of the research revealed that the implementation of religious and moral values ​​in early childhood at Kindergarten IT Bunayya 7 Laut Dendang Village, Percut Sei Tuan District, Deli Serdang District includes the Qur'an Ilham Wa Ruhan Program, namely a program to teach children from an early age about the verses of Al -Quran. Apart from that, there is also an Al-Quran memorization program, namely a program for children to memorize verses of the Al-Quran that have been taught by their teachers and then deposit them with their respective teachers. Next there is the clean and charity Friday program, namely a cleanliness program starting from something as simple as cleaning your nails, body and clothes. Apart from that, children are also taught to clean the environment. Lastly, the eating habits habituation program, namely schools provide healthy food to children that does not contain micin, etc. Apart from that, the teacher also teaches good eating habits like the Sunnah of the Prophet.